Analysis of Risk Factors Related To The Incidence of Type II Diabetes Mellitus at The Kolongan Health Center, North Minahasa Regency - Lotulung, Cindy Celine; Wariki, Windy Mariane Virenia; Korompis, Grace Esther Caroline (Asian Journal of Social and Humanities, 2025)
The aim of this study is to analyze the risk factors of type II diabetes mellitus at Kolongan Public Health Center, North Minahasa Regency. This research is an analytical observational study with a case-control approach matched by gender. The study was conducted at the Kolongan Public Health Center, North Minahasa Regency, during February–March 2025. The population consisted of 505 respondents diagnosed with Type II Diabetes Mellitus from January to December 2024. The sample was selected using a 1:1 ratio between the case group and the control group, based on the Lemeshow formula (1997) for matched case-control studies, resulting in a minimum required sample of 63 cases and 63 controls. Bivariate analysis using the Chi-Square Test and Logistic Regression Test showed a significant relationship between age and the incidence of type II diabetes mellitus (p-value = 0.005; OR = 2.985). A significant association was also found between family history and the incidence of type II diabetes mellitus (p-value = 0.001; OR = 3.520). However, no significant relationship was found between physical activity and the incidence of type II diabetes mellitus (p-value = 0.251; OR = 1.378). The conclusion of this study is that age and family history are associated with the incidence of type II diabetes mellitus at the Kolongan Public Health Center, North Minahasa Regency. Meanwhile, physical activity is not associated with the incidence of type II diabetes mellitus at the same location.